A Business Model Approach to Realizing Opportunities and Overcoming Barriers in E-Health - Francis Pereira; Elizabeth Fife (International Telecommunications Society (ITS), 2018)
A global and growing shortage of medical doctors and nurses, exacerbated by increasing life expectancy, is generating greater cost pressures on health care around the world. Many industry analysts and health care professionals have argued that early detection and preventive care, as well as education, is a solution to the escalating costs of medical care. In this respect, Telemedicine can help alleviate these pressures, as well as extend medical services to under-served or unserved areas. Despite rapid advancement in remote sensor technologies in the last 10 years, its relatively slow adoption suggests the presence of barriers and challenges. As such, while tele-health offers significant advantages, its limited use suggests potential divergences in "business models" of the key players in the health industry, specifically, health care providers and insurers, and other stake-holders. This paper uses the VISOR Business Model, as an organizing framework, to elucidate the value proposition that e-health offers to the U.S. healthcare environment. More importantly, we identify the barriers, as viewed through the "VISOR lens," that need to be addressed so as to facilitate tele health's adoption, widespread use and success. Traditional discussions on e-Health have revolved around the health provider, insurance company and patient. However since the benefits of E-Health accrue to other parties, other non-traditional stakeholders have to be included. These would include the national telecommunications service providers, equipment manufacturers, software services providers and major corporations, with one these stakeholders perhaps acting as a "keystone" player. Successfully deployment of e-Health will perhaps revolve around a "keystone" player in the comprehensive eco-system driving the initiative, as well as identifying the right revenue model, organizational structure and, perhaps more importantly the stakeholders.
Keywords: 330